FREQUENCY, IMAGINIG PATTERNS AND PITFALLS IN BLUNT ABDOMINAL TRAUMA, A SINGLE CENTER EXPERIENCE STUDY - Ramadani, Pranvera; Dimitrovska, Maja Jakimovska; Jovanovska, Elizabeta Stojovska; Nikodinovski, Violeta Vasilevska; Dodevski, Ace (Journal of Morphological Sciences; Vol 6 No 2 (2023): JMS, 2023)
Blunt abdominal trauma is a life-threatening condition and imaging is key in identifying the next step in patient management. The objective of this study is to determine the frequency and pitfalls of blunt abdominal trauma findings in multiphasic Multidetector Computed Tomographic (MDCT) examinations in patients with road traffic injuries and falls in the setting of polytrauma. After institutional review board approval with a waiver of informed consent was obtained, a retrospective study was performed focusing on a three-month period in 2023, from May to July in patients referred to our department with the diagnosis of superficial injuries involving multiple body regions â€“ T00. A review of the Picture Archiving and Communication System (PACS), the electronic medical records and dictated reports identified patients who met the criteria of abdominal blunt trauma. A total number of 321 patients were identified, who met the criteria of superficial injuries involving multiple body regions (average age, 37.5 years). 220 patients were male. 2,8% (9 patients) had imaging findings of blunt abdominal trauma. 55,5 % of patients had spleen traumatic injuries, the remaining percentage was liver, kidney, retroperitoneal hematoma and isolated free abdominal fluid. MDCT and administration of intra venous contrast is crucial in recognizing many of the spectral findings blunt abdominal trauma. A protocol of biphasic â€œCombiâ€ scan should be implemented in order to minimize radiation exposure and duration of the scan. Multiphasic Computed Tomography (CT) acquisition is key to avoid pitfalls. Key words: Blunt abdominal trauma, Multiphasic MDCT, spleen injury, liver injury, kidney injury, retroperitoneal hematoma, isolated free abdominal fluid.